LITERARY TOURISM IN THE TIME OF COVID-19: AN APPROACH STUDY IN "OEDIPUS THE KING" - Athraa Abdul Bari Kadhim; Asst. Prof. Zainab Hussein Alwan (American Journals Publishing, 2024)
Literary tourism is an essential type which is tied up with artistic works. It is a relatively new subject and is still under-researched. With the emergence of Covid-19, people resort to travel spiritually and emotionally visiting various places.The current study aims to investigate the utilization of literary tourism in some selected texts of Sophocles' Play "Oedipus the King" with regard to COVID-19.
Keywords: Literary Tourism, COVID-19,